Working to Change Systems: Repatriated U.S. Trained Japanese Physicians and the Reform of Generalist Fields in Japan. Issue 4 (8th August 2019) - Heist, Brian S.; Matsubara Torok, Haruka; Michael Elnicki, D.
Abstract: Phenomenon : Internationally, efforts to produce an adequate supply of effective generalist physicians commonly encounter resistance. Achieving reform requires changes in educational and clinical practice cultures, and clinician educators play a central role in championing change. In Japan, training in generalist fields has historically been lacking, but for decades the government has advocated alignment with Western models. Meanwhile, some Japanese physicians have pursued U.S. training in generalist fields with intention to help change the clinical education and practice systems back in Japan. This study examines the endeavors of repatriated Japanese International Medical Graduates and provides a lens to understanding national challenges with reform and insights into strategizing next steps. Approach : Individual, semi-structured interviews were conducted with 19 purposively sampled Japanese IMGs who had repatriated across Japan after completing U.S. clinical residency in generalist fields. Iterative data collection and thematic analyses were performed using constant comparison. Findings : Participants identified Japanese medical universities and public sectors as steeped in traditions with systemic inertia. In turn, participants described well-informed career decision making involving connections and teammates, which commonly resulted in employment at new or smaller hospitals. Education-related efforts prioritized direct clinical work with physician trainees in the hope of building expansive lineages of educators. Main challenges were Japanese structural and cultural incongruences with Western generalist-based clinical practice. Participants described a competitive relationship with the long-standing ikyoku-based postgraduate education model and associated organ-based organization of clinical practice. Insights : Japanese IMG championing of clinical education and practice in generalist fields is largely marginalized within Japan's clinical education and practice landscape. National-level reform will require transforming or displacing the structurally and culturally rooted traditional infrastructure. Specific measures must be culturally nuanced but likely include those proven effective for similar reforms elsewhere. Based on Japan's national cultural characteristics, sustained leadership is anticipated to be particularly important.